Management Control Systems and Innovation: A case study enlightened by institutional theory - Barros, R. S.; Ferreira, A. (XVIII Encontro Internacional da AECA, 2018)
Prior research on the role of Management Control Systems (MCS) in innovation has highlighted the importance of these systems. However, how and why MCS can shape the behaviour toward innovation remain broadly unanswered. This study introduces institutional theory to provide a theoretical background and enlightenment on these matters. To obtain a holistic picture an exploratory and explanatory case study on Alpha, an innovative branch of a large Portuguese industrial group was conducted. At the end, the results informed a model that theorizes how and why MCS can drive individuals to innovative associated behaviours through dimensions of communication and guidance and focus.